Potential contribution of the uterine microbiome in the development of endometrial cancer. Issue 1 (December 2016) - Walther-António, Marina; Chen, Jun; Multinu, Francesco; Hokenstad, Alexis; Distad, Tammy; Cheek, E.; Keeney, Gary; Creedon, Douglas; Nelson, Heidi; Mariani, Andrea; Chia, Nicholas
Abstract Background Endometrial cancer studies have led to a number of well-defined but mechanistically unconnected genetic and environmental risk factors. One of the emerging modulators between environmental triggers and genetic expression is the microbiome. We set out to inquire about the composition of the uterine microbiome and its putative role in endometrial cancer. Methods We undertook a study of the microbiome in samples taken from different locations along the female reproductive tract in patients with endometrial cancer (n = 17), patients with endometrial hyperplasia (endometrial cancer precursor, n = 4), and patients afflicted with benign uterine conditions (n = 10). Vaginal, cervical, Fallopian, ovarian, peritoneal, and urine samples were collected aseptically both in the operating room and the pathology laboratory. DNA extraction was followed by amplification and high-throughput next generation sequencing (MiSeq) of the 16S rDNA V3-V5 region to identify the microbiota present. Microbiota data were summarized using both α-diversity to reflect species richness and evenness within bacterial populations and β-diversity to reflect the shared diversity between bacterial populations. Statistical significance was determined through the use of multiple testing, including the generalized mixed-effects model. Results The microbiome sequencing (16S rDNA V3-V5 region) revealed that the microbiomes of all organs (vagina, cervix, Fallopian tubes, and ovaries) are significantly correlated (p < 0.001) and that there is a structural microbiome shift in the cancer and hyperplasia cases, distinguishable from the benign cases (p = 0.01). Several taxa were found to be significantly enriched in samples belonging to the endometrial cancer cohort: Firmicutes (Anaerostipes, ph2, Dialister, Peptoniphilus, 1–68, Ruminococcus, andAnaerotruncus ), Spirochaetes (Treponema ), Actinobacteria (Atopobium ), Bacteroidetes (Bacteroides andPorphyromonas ), and Proteobacteria (Arthrospira ). Of particular relevance, the simultaneous presence ofAtopobium vaginae and an uncultured representative of thePorphyromonas sp. (99 % match toP. somerae ) were found to be associated with disease status, especially if combined with a high vaginal pH (>4.5). Conclusions Our results suggest that the detection ofA. vaginae and the identifiedPorphyromonas sp. in the gynecologic tract combined with a high vaginal pH is statistically associated with the presence of endometrial cancer. Given the documented association of the identified microorganisms with other pathologies, these findings raise the possibility of a microbiome role in the manifestation, etiology, or progression of endometrial cancer that should be further investigated.